Distribución del género Diplodon (Mollusca: Bivalvia: Hyriidae) en la Cuenca del Plata (Argentina) mediante el uso de Colecciones Biológicas - Torres, Santiago Hernan (2013)
Pearly freshwater mussels (“naiads”) are infaunal species endemic to the Neotropical region and belong to the families Hyriidae and Etheriidae. Habitat alteration and competition with invasive species such as Corbicula fluminea and Limnoperna fortunei impact on their natural populations. This communication presents the start of a research project on the geographical distribution of Diplodon species in Argentina. These species are an important component of the infauna in lotic and lentic water bodies,-. They live in muddy and sandy-loam soils and, unusually, in hard substrate. They are filter feeders with an important role as recyclers of organic matter. Knowing the distribution of the bivalves belonging to the genus Diplodon in Argentine allows potential priority conservation areas to be recognised. On the basis of the available literature and the specimens of the species of the genus Diplodon conserved in the malacological collection in Museo de La Plata (FCNyM -UNLP), a data matrix was made. The data matrix includes specimen identification, the collection where it is deposited, the catalogue number, locality and date of collection. Each locality was situated by using maps of Argentina and literature reviews in GoogleEarth satellite imagery and the coordinates for each point were mapped. The results showed the distribution of native species and thus it was possible to discuss how much the two species of bivalve invaders overlap and the relationship with the impact of human activities.